Beyond Chiral Organic (p-Block) Chromophores for Circularly Polarized Luminescence: The Success of d-Block and f-Block Chiral Complexes - Doistau, Benjamin; Jiménez, Juan-Ramón; Piguet, Claude (Frontiers in Chemistry, 2020)
Chiral molecules are essential for the development of advanced technological applications in spintronic and photonic. The best systems should produce large Circularly Polarized Luminescence (CPL) as estimated by their dissymmetry factor (glum), which can reach the maximum values of -2 ≤ glum ≤ 2 when either pure right- or left-handed polarized light is emitted after standard excitation. For matching this requirement, theoretical considerations indicate that optical transitions with large magnetic and weak electric transition dipole moments represent the holy grail of CPL. Because of their detrimental strong and allowed electric dipole transitions, popular chiral emissive organic molecules display generally moderate dissymmetry factors (10-5 ≤ glum ≤ 10-3). However, recent efforts in this field show that glum can be significantly enhanced when the chiral organic activators are part of chiral supramolecular assemblies or of liquid crystalline materials. At the other extreme, chiral EuIII and SmIII based complexes, which possess intra-shell parity forbidden electric, but allowed magnetic dipole transitions have yielded the largest dissymmetry factor reported so far with glum ~ 1.38. Consequently, 4f-based metal complexes with strong CPL are currently the best candidates for potential technological applications. They however suffer from the need for highly pure samples and from considerable production costs. In this context, chiral earth-abundant and cheap d-block metal complexes benefit from a renewed interest according that their CPL signal can be optimized despite the larger covalency displayed by d-block cations compared with 4f-block analogues. This essay thus aims at providing a minimum overview of the theoretical aspects rationalizing circularly polarized luminescence and their exploitation for the design of chiral emissive metal complexes with strong CPL. Beyond the corroboration that f-f transitions are ideal candidates for generating large dissymmetry factors, a special attention is focused on the recent attempts to use chiral CrIII based complexes that reach values of glum up to 0.2. This could pave the way for replacing high cost rare-earth with cheap transition metals for CPL applications.